2020
DOI: 10.4236/ajps.2020.113034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adjuvants on the Efficacy of Tolpyralate plus Atrazine for the Control of Annual Grass and Broadleaf Weeds in Corn with and without Roundup WeatherMAX<sup>®</sup>

Abstract: Tolpyralate is a new HPPD-inhibiting herbicide that is efficacious on annual grass and broadleaf weed species in corn. For maximum herbicide performance of tolpyralate, it is recommended that atrazine is tank mixed with tolpyralate along with the adjuvants methylated seed oil concentrate (MSO) plus urea ammonia nitrate (UAN). A common use pattern of tolpyralate plus atrazine will be in a tank mix with Roundup WeatherMAX® due to the high proportion of corn acres that are seeded to Roundup Ready® hybrids in East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 25 publications
10
25
0
Order By: Relevance
“…In the current study, velvetleaf control was 89-100% at 2, 4, and 8 WAA when tolpyralate + bromoxynil was applied with and without the addition of adjuvants. This is comparable to previous studies that reported velvetleaf control of 86-99% with tolpyralate + MSO Concentrate®, tolpyralate + atrazine + MSO Concentrate®, tolpyralate + atrazine + glyphosate, and tolpyralate + atrazine + glyphosate + MSO Concentrate® (Langdon et al, 2020;Metzger et al, 2018). In agreement with the control data, the density and dry biomass reduction of velvetleaf with tolpyralate + bromoxynil was similar among the different adjuvant treatments.…”
Section: Velvetleafsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, velvetleaf control was 89-100% at 2, 4, and 8 WAA when tolpyralate + bromoxynil was applied with and without the addition of adjuvants. This is comparable to previous studies that reported velvetleaf control of 86-99% with tolpyralate + MSO Concentrate®, tolpyralate + atrazine + MSO Concentrate®, tolpyralate + atrazine + glyphosate, and tolpyralate + atrazine + glyphosate + MSO Concentrate® (Langdon et al, 2020;Metzger et al, 2018). In agreement with the control data, the density and dry biomass reduction of velvetleaf with tolpyralate + bromoxynil was similar among the different adjuvant treatments.…”
Section: Velvetleafsupporting
confidence: 91%
“…Similarly, Harbour et al (2003) found that four different surfactants did not improve kochia or Russian thistle control with bromoxynil. In contrast, Langdon et al (2020) reported that velvetleaf control with tolpyralate + atrazine was enhanced with the addition of MSO Concentrate®; however, when glyphosate was co-applied with tolpyralate + atrazine, MSO Concentrate® did not improve velvetleaf control. Previous research has reported >90% velvetleaf control with bromoxynil applied without the addition of an adjuvant, which may have contributed to the inability to detect a benefit of adjuvant addition to tolpyralate + bromoxynil (Corbett et al, 2004).…”
Section: Velvetleafmentioning
confidence: 90%
See 3 more Smart Citations